ANALISIS BUTIR SOAL URAIAN ETNOMATEMATIKA BERNUANSA KOTA TANGERANG PADA MATERI MATEMATIKA - Dzil Ikram, Fadhli; Setiyadi, Desi; Zubaidi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the quality of ethnomathematics-based mathematics essay items using Tangerang City local culture in mathematics learning at Madrasah Ibtidaiyah. This study used a quantitative approach with a descriptive method. The research subjects consisted of 10 essay items containing local cultural contexts of Tangerang City and 35 fifth-grade Madrasah Ibtidaiyah students. Data were collected through documentation studies of item grids, scoring rubrics, and students’ answer sheets. Data analysis was conducted through item validity, reliability, difficulty level, and discrimination index tests. The item validity test showed that all items from Q1 to Q10 were valid. The reliability test obtained a Cronbach’s Alpha value of 0.970, which belonged to the very high category. The difficulty level analysis showed that all items were in the moderate category. The discrimination index analysis showed that all items were in the good category. These findings indicate that ethnomathematics-based essay items are feasible for use as mathematics learning evaluation instruments because they meet the empirical criteria of validity, reliability, difficulty level, and discrimination index.